COOPERATIVES AND THEIR CONTRIBUTION TO THE DEVELOPMENT OF MICRO, SMALL AND MEDIUM ENTERPRISES - Kusuma Candra Kirana; I.Soni Kuriawan; Lucia Fransiska Noviani (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2021)
The purpose of this study was to determine the effect of organizational culture and individual characteristics on career development with motivation as an intervening variable. The object of this research is the Yogyakarta City Health Office. This study used a descriptive study using a quantitative approach with a total sample size of 35 respondents. The results of this study indicate that: Organizational culture has a positive and significant effect on motivation, Individual characteristics have a positive and significant effect on motivation, motivation has a positive and significant effect on Career Development, Organizational Culture has a positive and significant effect on Career Development,Individual Characteristics Culture has a positive and significant effect on Career Development, there is no positive and significant influence between Organizational Culture on Career Development with Motivation as an intervening variable, there is no positive and significant effect between Individual Characteristics on Career Development with Motivation as an intervening variable.